Strategies for Increasing GRDP Contribution to the Agricultural Sector in Banyuwangi District - Prapti, Kanthi Pangestuning (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The economic distribution of Banyuwangi is almost one third of which is in the Agriculture, Forestry, and Fisheries categories. However, not all programs in the sub-sector can be implemented so that agricultural development based on the leading sub-sector is expected to be a priority. Therefore, strategic steps are needed in the development of the sub-sector in the future. The research method used is descriptive quantitative. The results showed: 1) The agricultural sector for food crops gave a very large contribution to Gross Regional Domestic Product (GRDP) every year with an average contribution for 5 years of 30.09%, followed by the fishery sub-sector with its contribution of 19.86%, livestock by 19.65%, plantations by 15.75%, horticulture by 9.94%, forestry and logging by 3.60% and agricultural and hunting services with a contribution of 1.11%; 2) The agricultural sector development strategy in increasing GRDP in Banyuwangi Regency that must be applied in this condition is to support an aggressive growth policy (growth oriented strategy).